Risks to job quality from digital technologies: Are industrial relations in Europe ready for the challenge? - Janine Berg; Francis Green; Laura Nurski; David A. Spencer (Bruegel, 2022)
We examine the job quality effects of new digital technologies in Europe, using the framework of seven job quality 'domains': pay, working time quality, prospects, skills and discretion, work intensity, social environment and physical environment. The theoretical effects from new technology are ambivalent for all domains. Data on robot shocks matched to the European Working Conditions Surveys for 2010 and 2015 is used to generate empirical estimates, which show significant aggregate negative effects in three domains, and a positive effect in one. Some negative effects are enhanced where there is below-median collective bargaining. In light of these analyses, and in order to think through the challenge of regulating the development and implementation of all forms of digital technologies, we review regulations in several European countries. Drawing on the principles of human-centred design, we advance the general hypothesis that worker participation is important for securing good job quality outcomes, at both the innovation and adoption stages. We also consider the application to the regulation of job quality of national and supra-national data protection legislation. In these ways, the paper extends the debate about the future of work beyond employment and pay, to a consideration of job quality more broadly.
Keywords: 330; future of work